2020
DOI: 10.1055/a-1167-4284
|View full text |Cite
|
Sign up to set email alerts
|

Artemisiae Iwayomogii Herba Inhibits Growth, Motility, and the PI3K/AKT/mTOR Signaling Pathway in Hepatocellular Carcinoma Cells

Abstract: Abstract Artemisia gmelinii (Artemisia iwayomogi) has been used in traditional medicine to cure various infectious diseases such as cholecystitis, hepatitis, and jaundice. In this study, the Artemisiae Iwayomogii Herba ethanol extract was investigated for the ability to inhibit growth of hepatocellular carcinoma and its underlying mechanism involved. The antiproliferative effect of Artemisiae Iwayomogii Herba ethanol extract was evaluated using cell viability and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…After 4 weeks of feeding pubertal mice with different concentrations of lysine (0%, 0.025%, 0.05% and 0.1%) in drinking water, the total proteins of mammary gland were extracted. The PI3K/AKT/mTOR signalling pathway mainly participates in the proliferation, growth, motility, metabolism and other physiological activities in response to extracellular stimuli (Kim et al, 2020;Sharma et al, 2017). In this study, we found that lysine activated the PI3K/AKT/mTOR signalling pathway.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…After 4 weeks of feeding pubertal mice with different concentrations of lysine (0%, 0.025%, 0.05% and 0.1%) in drinking water, the total proteins of mammary gland were extracted. The PI3K/AKT/mTOR signalling pathway mainly participates in the proliferation, growth, motility, metabolism and other physiological activities in response to extracellular stimuli (Kim et al, 2020;Sharma et al, 2017). In this study, we found that lysine activated the PI3K/AKT/mTOR signalling pathway.…”
Section: Discussionsupporting
confidence: 51%
“…The PI3K/AKT/mTOR signalling pathway mainly participates in the proliferation, growth, motility, metabolism and other physiological activities in response to extracellular stimuli (Kim et al, 2020; Sharma et al, 2017). In this study, we found that lysine activated the PI3K/AKT/mTOR signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulating evidences have suggested the participation of the activated PI3K/Akt pathway in the growth-promoting effects of PTEN in HCC [ 19 22 ]. The blockade of the PI3K/AKT/mTOR pathway can help efficiently induce apoptosis and inhibit the growth, migration, and invasion of human HCC cells [ 23 ]. Likewise, in our study, high expression of PI3K was also observed in HCC tissues and delivery of a lentiviral vector containing human PTEN exerted inhibitory effects on HCC cell malignant behaviors while inducing apoptosis by inhibiting the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HCC is intrinsically resistant to a number of cytotoxic agents. Natural products are generally considered as safe supplier for biomedical applications due to their low toxicity ( Kim et al, 2020 ). In cancer therapy, naturally derived agents represent the largest portion of approved anti-tumor drugs ( Newman and Cragg, 2016 ).…”
Section: Discussionmentioning
confidence: 99%